Personalized system of instruction in cyberspace. - Pear, Joseph J.; Crone-Todd, Darlene E. (Journal of Applied Behavior Analysis)
Four different undergraduate psychology courses with no allotted classroom time slots were taught in the same term by means of a computer-based version of Keller's personalized system of instruction (PSI), called computer-aided personalized system of instruction (CAPSI). Students' performance and ratings indicate that CAPSI is a viable on-line educational method. Reprinted by permission of the publisher.